Visual design concepts for mobile games - Carman, Christopher (CRC Press, Taylor & Francis Group, 2018)
This book is geared towards both students as well as professionals who are looking to enter the mobile (tablet/smartphone) and PC (personal computer) industry as concept artists (for both 2D and 3D production pipelines) or 2D production artists (game-ready assets). This book is not specifically focused on game design or game development and is also not a 3D modeling or animation guide. The concept, theme, and style of these assets, as well as the world they inhabit, will be completely up to the individual artist.